The use of rocks to improve family agriculture in Brazil - Theodoro, Suzi H. (2006)
During the second half of the 20th century, the introduction of new chemical agriculture technologies brought about a revolution in food production, but this has also cause deep deterioration in our relationships with the natural environment. In developing tropical countries, record yields were accompanied by rural exodus, widespread deforestation and loss of topsoil. The stonemeal research described herein is an alternative to such practices as it is an environmental friendly and socially responsible technology based on soil rejuvenation and conservation by means of the addition of natural rock powders that are rich in phosphorous, calcium, magnesium, potassium and micronutrients. The research adopted an inter-disciplinary approach and was conducted among small farmers of a rural community located in the state of Minas Gerais, Brazil. The major goal was to demonstrate that there is a harmless cheap and simple alternative to fertilizing degraded or impoverished soils, which allow farmers to sustain high productivity and to remain on their plots of land. Results have confirmed the economic, environmental and productive feasibility and advantage of the stonemeal technique for corn, rise, manioc, sugar cane and horticultural species, when compared to the use of chemical fertilizers. The fertilization of the soil with rocks, allows the understanding of the natural processes, which maintain production levels while building a sustainable fertile soil.